"Dislexic sight words" (dsw) e intervenção fonoaudiológica em escolares com dislexia. - Meira, Luciana Cidrim Calado (2019)
Difficulties in the field of orthographic knowledge can impact formal schooling in several measures, since reading and writing are fundamental throughout the academic course. The more transparent relation between phonology and orthography, with regard to the Portuguese language, seems to produce less serious problems for reading. In the case of dyslexia, the focus of the studies has been on reading difficulties, with less research on spelling processing. This research aims to investigate the viability of a list of 60 words, often incorrectly written by students with dyslexia, inspired by the methodology that uses lists of sight words in the teaching of high frequency words in the English language, with specific objectives to categorize and compare the errors observed in the writing of words by schoolchildren with and without dyslexia. Sixty students, 30 with dyslexia (GD) and 30 without dyslexia (GDS), from the 3rd to the 6th year of elementary school, were divided into eight groups according to the year of schooling: GD3, GD4, GD5 and GD6 and GSD3, GSD4, GSD5 and GSD6 and 30 professionals who work with schoolchildren with disorders and learning disorders and dyslexia.The first stage of the data collection consisted of the application of a questionnaire to 30 professionals, who were asked to declare 40 words frequently misspelled by students with dyslexia. Next, a list of 60 words most often quoted by professionals was designed. All GD and GSD students performed a 60-word dictation. The results of this research allowed us to conclude that there was a statistically significant difference in the spelling performance of the group of schoolchildren with dyslexia - GD - compared to the group of schoolchildren without dyslexia - GSD - when writing the list of 60 words called 'Dyslexic Sight Words'. The number of words written incorrectly decreased throughout the school years in both groups, but in GD the difficulties persist for a longer time, observing a greater variety of orthographic forms. The high number of spelling errors made by the GD in writing words that seem to be common in their daily lives makes it possible to use word lists to support the teaching of spelling for dyslexic schoolchildren. Based on the orthographic classification of Zorzi (1998), GD students presented a greater number of errors by multiple representations (related to irregularities in the phoneme and grapheme relationship), by oral influence that is (influence of speech patterns in writing), absence of the acute accent and absence of the tilde and deaf exchanges (difficulties in distinguishing the sound aspects that differentiate one phoneme from the other). In the GSD students, the most frequent errors were practically the same as the GD, except for the sound-deafness and absence of the tilde. The present study contributed to the development of applications that include activities to support therapy in the spelling difficulties of students with dyslexia, since teaching spelling with the support of technological tools may be more attractive for students with learning difficulties, especially the dyslexia.